Sugarcane bagasse: Production, composition, properties, and feedstock potential - Melati, Ranieri Bueno [UNESP]; Schmatz, Alison Andrei [UNESP]; Pagnocca, Fernando Carlos [UNESP]; Contiero, Jonas [UNESP]; Brienzo, Michel [UNESP] (My University, 2017)
Sugarcane is widely cultivated in tropical and subtropical countries around the world, with increasing annual production. The largest sugarcane producing countries are, in millions of tons: Brazil (721), India (347), China (123), and Thailand (96). Sugarcane is grown mainly for sucrose extraction for the production of sugar and ethanol. However, the sugarcane culture is responsible for generating, as a residue, the sugarcane bagasse (140 kg of bagasse are produced for every ton of sugarcane processed), and thus this is the most abundant lignocellulosic residue in Brazilian agriculture. The sugarcane bagasse, a byproduct, is nowadays valued by producers from the sugar-alcohol sector, since it is presented as a main feedstock source for bioenergy and biofuel production. The sugarcane bagasse is mostly composed by cellulose/glucan, a linear polysaccharide made up by ß-1,4-D-glucose unities; hemicellulose, a heterogeneous polysaccharide composed by differentiated amounts of hexose and pentose sugars; and lignin, an aromatic macromolecule, which gives a high complexity and recalcitrance to the lignocellulosic structure. This biomass can be used to generate electrical energy through thermal conversion, and has several potential and industrial applications: as a nutritive additive for ruminant ration, as feedstock for the production of second generation ethanol, among other potential uses. These applications show that the use of sugarcane bagasse may represent economic and environmental importance for the producing countries. In this context, this chapter presented the sugarcane production and its social impacts, bagasse chemical composition and properties, and the main potential applications that have been studied in industrial scale.